Vascular endothelial growth factor single nucleotide polymorphisms and haplotypes in pre-eclampsia: A case-control study. (September 2017) - Ben Ali Gannoun, Marwa; Al-Madhi, Safa A.; Zitouni, Hedia; Raguema, Nozha; Meddeb, Sawsen; Hachena Ben Ali, Feten; Mahjoub, Touhami; Almawi, Wassim Y.
Highlights: We genotyped ten genetic markers in the VEGF-A gene with preeclampsia (PE). Lack of association of the genotypes of VEGFA SNPs with PE. Positive association and negative association of haplotypes with PE were demonstrated. Increased PE severity in ATGCCAA haplotype carriers. Reduced PE severity associated with both ATGCCGG and CCAGCAA haplotypes. Abstract: An association between vascular endothelial growth factor ( VEGFA ) gene variants and altered VEGF secretion and preeclampsia (PE) were described, often with inconclusive findings. An ethnic contribution to the association of VEGFA polymorphisms with PE and its associated features was also suggested. To investigate whether common VEGFA single nucleotide polymorphisms (SNP) are linked with PE and associated features in Tunisian women. A case-control study involving 300 women with PE, and 300 age-matched control women. Genotyping of VEGFA rs833052, rs699947, rs833061, rs1570360, rs2010963, rs25648, rs833068, rs833070, rs3025020, and rs3025039 SNPs was done by real-time PCR. Minor allele frequency (MAF) of rs833052, rs699947, rs833061, rs1570360, rs2010963, rs25648, rs833068, rs833070, rs3025020, and rs3025039 VEGFA SNP, were not significantly different between PE cases and control women. In addition, there was lack of association of the genotypes of VEGFA SNPs with PE, irrespective of the genetic model used. Seven-locus (rs699947, rs833061, rs1570360, rs2010963, rs25648, rs833068 and rs833070) haplotype analysis demonstrated positive association of ATGCCAA, ACAGCAG and CCAGCGG, and negative association of CCAGCAA and ATGCCGG haplotypes with PE, all of which except for ACAGCAG remained associated with PE after correcting for multiple comparisons. Increased and reduced PE severity was associated with ATGCCAA, and with ATGCCGG and CCAGCAA haplotypes, respectively. Furthermore, carriage of CCGGTAG haplotype was associated with reduced risk of PE. Our study suggests that VEGFA haplotypes, more so than individual SNPs, play a role in PE pathogenesis in Tunisian women. These findings need confirmation in other ethnic populations.